2001
DOI: 10.1103/physreve.63.021909
|View full text |Cite
|
Sign up to set email alerts
|

Helix-coil transition in homopolypeptides under stretching

Abstract: We consider the effect of an external applied force on the alpha-helix-coil transition of a single-stranded homopolypeptide chain. An annealed scenario is assumed, where the building amino acid monomers may interconvert between random-coiled and ordered alpha-helical configurations. By exact evaluation of the partition function of the freely jointed chain with helix-coil internal degrees of freedom in the thermodynamic limit, we obtain the result that the stress-strain characteristic has an asymmetrical sigmoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 53 publications
5
77
0
Order By: Relevance
“…Comparing to spherical atoms and small molecules, how flexible chain transform into rigid conformational ordered segment (COS) is the most peculiar rate-limited step in polymer crystallization, which can be overcome by OCB with the cooperative effect of COS with rotational symmetry at quiescent condition. As flow can induce conformational order like gauche-trans or coil-helix transitions [27,28] and align chain segments in parallel, different structural intermediates may emerge, resulting in different kinetic pathways of nucleation as comparing to that at quiescent condition.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing to spherical atoms and small molecules, how flexible chain transform into rigid conformational ordered segment (COS) is the most peculiar rate-limited step in polymer crystallization, which can be overcome by OCB with the cooperative effect of COS with rotational symmetry at quiescent condition. As flow can induce conformational order like gauche-trans or coil-helix transitions [27,28] and align chain segments in parallel, different structural intermediates may emerge, resulting in different kinetic pathways of nucleation as comparing to that at quiescent condition.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism must be the enhanced statistical weight for finding a segment in its longer nonnative state. The applied force thereby accesses a reservoir of chain length built into each segment; such a mechanism has been studied in detail by Tamashiro and Pincus [43] although that work ignored the role of the tangent vector fluctuations. These fluctu- ations should only enhance the nonlinear growth of the effective chain compliance.…”
Section: Force Extension Relations: Small Forcesmentioning
confidence: 99%
“…To account for such (two-state) internal degrees of freedom along the chain, workers have employed the helix/coil (HC) model [40]. This model has been used to study a class of protein conformational transitions [41,42] in solution and under tension [43].…”
Section: The Helix-coil Worm-like Chainmentioning
confidence: 99%
“…The transformation from flexible polymer chains into conformationally rigid, ordered crystalline segments is the most critical step for polymer crystallization. As predicted by theory, imposing flow can promote the formation of helices through coil‐helix transition because of entropic reduction, which may further organize into the precursors observed in flow‐induced crystallization . Following this line, several groups have applied spectroscopic methods, like Raman and infrared (IR) spectroscopy, to investigate the flow‐induced conformational ordering.…”
Section: Flow‐induced Crystallization Of Polymermentioning
confidence: 96%
“…Based on the above experimental observations, a schematic multi-scale ordering process for flow-induced crystallization was proposed by Su et al [82] (see Figure 16), which showed a sequential ordering process as the conformational order-density fluctuation-preordering-crystallization. Imposing flow on entangled polymer melts leads to intra-chain conformational ordering or coil-helical transition, which has been demonstrated by both theoretical predictions [79] and experimental observations mainly from in-situ spectroscopic methods. [82][83][84][85] Flow-induced coil-helical transition has also been confirmed by molecular dynamic computer simulations.…”
Section: Furthermore Different Crystalline Modifications and Morpholmentioning
confidence: 99%